Pertumbuhan Tunas Baru pada Pembungaan Anggrek Bulan (Phalaenopsis amabilis) melalui Stimulasi Bawang merah (Allium cepa L.) pada mata tunas - Zahra Fauziah Syuhada, Mutiara; Hernawati, Diana; Nuryadin, Egi (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
Moon orchid is a member of the Orchidaceae family which is a seed plant and belongs to epiphytic orchids that attach to the host. Moon orchid is also one of the most popular orchids among the public because of the beauty of its large flowers and can last two to 4 months. However, the difficulty of re-flowering in moon orchid is one of the problems. This study aims to determine the growth of new shoots on the flowering of moon orchids (Phalaenopsis amabilis) through stimulation of shallots (Allium cepa L.) on the bud eye. This research is a quantitative research with true experiment method. Data obtained in the form of numbers of observations for 12 weeks. With simple random sampling technique. The population in this study were moon orchid plants that have roots, stems and leaves. This moon orchid plant is 3.5 years old and totalling 25 individuals. While the sample in this study is the second bud eye moon orchid plants from the base of the stem. There is an effect of shallot extract on the bud eye to stimulate the growth of new buds on the flowering of moon orchids. This study shows that there is an effect of shallot extract on the bud eye to stimulate the growth of new shoots on the flowering of moon orchids. There is the best concentration for the growth of new shoot height on the moon orchid is at a concentration of 40% with an average growth of 6.36 cm, while for the growth of new shoot diameter on the moon orchid is at a concentration of 30% with an average growth of 0.608 cm. Thus, the best concentration for the growth of new shoots on the flowering of moon orchids is between 30% - 40% concentration